PENGARUH PENGGUNAAN MEDIA ANIMASI DIGITAL TERHADAP PEMAHAMAN OPERASI HITUNG DI KELAS II SD INPRES BONTOALA II - Nasrun; Ernawati; Nurazizah, St (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning media are important because they can increase students’ interest and motivation in learning, facilitate understanding of subject matter, and make the teaching and learning process more effective, efficient, and enjoyable. This study aims to determine the effect of using digital animation media on students’ understanding of addition and subtraction operations in grade II at SD Inpres Bontoala II, Gowa Regency. This research uses a quantitative approach with a pre-experimental design. The subjects of this study were all second-grade students at SD Inpres Bontoala II, Gowa Regency. The results showed that there was a significant effect on students’ understanding of addition and subtraction operations. This can be seen from the average pretest score of 71.05, which was still below the Minimum Mastery Criteria (KKM), and then increased in the posttest to an average score of 87.63, reaching the category of classical completeness. In addition, the results of the hypothesis test showed a significance value (Sig. 2-tailed) of 0.000 < 0.05, so H₀ was rejected and H₁ was accepted.